Enhanced Production of Cordycepin by Solid State Fermentation of Cordyceps militaris using Additives - Ting-Chi Wen (Science Faculty of Chiang Mai University, 2019)
Cordycepin is one of the most important bioactive compounds produced by the insect pathogenic fungus Cordyceps militaris. The effects of medium composition on enhanced production of cordycepin by C. militaris were investigated by changing the liquid supplement medium composition with rice medium in this study. Glucose, peptone, adenine, and histidine were optimized to improve the yield of cordycepin in 300 mL cylindrical glass bottles by solid state fermentation using response surface methodology. The optimum medium for cordycepin production using solid state fermentation were: glucose 26.25 g/L, peptone 26.25 g/L, adenine 7.50 g/L, histidine 4.50 g/L, MgSO4ื7H2O 0.1 g/L, and KH2PO4 0.1 g/L in liquid supplement medium. Under these conditions, the maximum cordycepin yield in the rice culture medium was 18.92 mg/g on 39 days, and this value is higher when compared to other reports using solid state fermentation. This is the first report for improving the cordycepin production by adding additives (nucleoside analogue and amino acid) in solid state fermentation by C. militaris. This method provides an effective way for increasing the cordycepin production by solid state fermentation.